2019
DOI: 10.21107/jaffa.v7i2.6721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Good Corporate Governance on Profitability

Abstract: The research aims to decide the effect of good corporate governance on profitability in banking companies listed on Indonesia stock exchange from 2016 to 2017. This researchwas an explanatory research, using secondary data. The sample was selected using the purposive sampling method, which resulted in a total of 28 sample companies. The data analysis used was multiple linear regression. The results show that the board of directors significantly affect profitability and independent commissioners does not signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The proportion of independent commissioners has no significant negative effect on tax aggressiveness. The results of this study are not in line with research (Ariawan & Setiawan, 2017;Fadli et al, 2016;Gloria & Apriwenni, 2020;Innocent & Gloria, 2018;Nilasari & Setiawan, 2019;Novitasari et al, 2017;Nugroho & Firmansyah, 2018;Sarpingah & Purba, Vol.2, No.9, August 2023 2019; Subarnas & Gunawan, 2019a;Vanesali & Kristanto, 2020). Manufacturing companies registered with IDX 2017-2021 have formally complied with OJK regulations No.33/POJK.04/2014 Article 20 paragraph 3 which stipulates that independent commissioners are at least 30% (thirty percent) of the total number of members of the board of commissioners, namely with an average the average proportion of independent commissioners is 40%.…”
Section: Methodscontrasting
confidence: 94%
“…The proportion of independent commissioners has no significant negative effect on tax aggressiveness. The results of this study are not in line with research (Ariawan & Setiawan, 2017;Fadli et al, 2016;Gloria & Apriwenni, 2020;Innocent & Gloria, 2018;Nilasari & Setiawan, 2019;Novitasari et al, 2017;Nugroho & Firmansyah, 2018;Sarpingah & Purba, Vol.2, No.9, August 2023 2019; Subarnas & Gunawan, 2019a;Vanesali & Kristanto, 2020). Manufacturing companies registered with IDX 2017-2021 have formally complied with OJK regulations No.33/POJK.04/2014 Article 20 paragraph 3 which stipulates that independent commissioners are at least 30% (thirty percent) of the total number of members of the board of commissioners, namely with an average the average proportion of independent commissioners is 40%.…”
Section: Methodscontrasting
confidence: 94%
“…The research of Ayuningtyas, et al (2020) also found insignificant and positive results. This study has the same results as research by Subarnas & Gunawan (2019), Aryani (2019), Putra & Fidiana (2017), Pangaribuan (2017).…”
Section: Discussionsupporting
confidence: 83%
“…This study has the same results and is align with the research of Subiyanti and Zannati (2019) which states that there is a negative insignificant effect of the independent board of commissioners on ROA. Research by Subarnas & Gunawan (2019), Aryani (2019), Merryana, et al (2019), Ayuningtyas, et al (2020), Dewi & Badjra (2017), Candradewi & Sedana (2016), Diyanty & Yusniar (2019), Solekhah & Efendi (2020), and Irma (2019) which also stated that the influence of independent commissioners was not significant on ROA and positive. Unlike the research conducted by Putri & Muid (2017), Tertius & Christiawan (2015) which stated a significant and negative effect.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations